2016
DOI: 10.1097/moh.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Is the D14 bone marrow in acute myeloid leukemia still the gold standard?

Abstract: Early bone marrow evaluation has a potential to personalize the induction regimen, but because of limitations of day 14 bone marrow results, earlier bone marrow evaluation or the use of flow cytometry to detect minor blast populations may improve remission prediction in AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Varying therapy regimens are used worldwide, that mostly differ in time and duration of chemotherapy administering [8]. The presented treatment model is also suitable for a planned comparison of different double induction concepts like TAD-HAM vs. S-HAM [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying therapy regimens are used worldwide, that mostly differ in time and duration of chemotherapy administering [8]. The presented treatment model is also suitable for a planned comparison of different double induction concepts like TAD-HAM vs. S-HAM [7].…”
Section: Discussionmentioning
confidence: 99%
“…Different 7 + 3 regimens are preferred depending on respective region, e.g. an evaluation process with potential re-induction in the United States compared to a preferred double induction in Europe [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ability to predict chemosensitivity with current prognostic models incorporating karyotype and mutations, initial demonstration of chemosensitivity requires a day 14 bone marrow aspirate and biopsy (D14BM) during induction treatment with cytarabine and anthracycline‐based regimens. While the D14BM is regularly used to predict achievement of complete remission (CR) for patients undergoing cytotoxic induction therapy, its utility and sensitivity have been questioned (Luger, ; Ofran, ). Several studies have found that D14BM evaluation may not be reliable in predicting induction outcome, leading to a false positive result in some cases, with patients achieving a CR without exposure to additional chemotherapy despite having residual blasts on D14BM (Norkin et al , ; Terry et al , ).…”
mentioning
confidence: 99%